Improved Husbandry and Management in Sheep Fattening for Youth and Women Sheep Fattening Groups - Wamatu, Jane; Zeleke, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
A training report on improved husbandry and management in sheep fattening for youth and women sheep fattening groups